2019
DOI: 10.1186/s13244-019-0808-5
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional imaging of acute gynaecologic disorders: CT and MRI findings with differential diagnosis—part I: corpus luteum and haemorrhagic ovarian cysts, genital causes of haemoperitoneum and adnexal torsion

Abstract: Acute gynaecologic disorders are commonly encountered in daily clinical practice of emergency departments (ED) and predominantly occur in reproductive-age women. Since clinical presentation may be nonspecific and physical findings are often inconclusive, imaging is required for a timely and accurate diagnosis. Although ultrasound is the ideal non-invasive first-line technique, nowadays multidetector computed tomography (CT) is extensively used in the ED, particularly when a non-gynaecologic disorder is suspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 71 publications
(130 reference statements)
0
7
0
Order By: Relevance
“…By contrast, in corpus luteal cyst rupture, the hemoperitoneum is more likely to appear in intermediate signal on T1-weighted sequence, with a sentinel clot in high signal (Fig. 4 ) [ 35 37 ].…”
Section: Gynecologic Complicationsmentioning
confidence: 99%
“…By contrast, in corpus luteal cyst rupture, the hemoperitoneum is more likely to appear in intermediate signal on T1-weighted sequence, with a sentinel clot in high signal (Fig. 4 ) [ 35 37 ].…”
Section: Gynecologic Complicationsmentioning
confidence: 99%
“…When the torsion is of low grade, it will first impair the venous and lymphatic drainage, making the arterial waveforms detectable [ 91 ]. After inconclusive US, MRI represents a better technique by which to assess suspected OT, depicting both direct and indirect findings more clearly [ 3 , 92 ]. A retrospective study, evaluating the diagnostic accuracy of MRI for OT in pregnancy, reported sensitivity, specificity, positive and negative predictive values of 100%, 77.8%, 90.5% and 100% [ 93 ].…”
Section: Urogenital Tract Diseasesmentioning
confidence: 99%
“…The pathognomonic and most specific feature is a twisting of the ovarian pedicle, presenting as a beak-like protrusion adjacent to the ovarian mass or to the enlarged ovary. However, it is only identified in less than one-third of patients through CT and MRI [ 92 , 94 ]. In the early stages, an asymmetric enlarged oedematous ovary with central follicular stromal and peripherally displaced follicles in a string-like appearance (“pearl string sign”) is well demonstrated by MRI, especially on T2-weighted sequences.…”
Section: Urogenital Tract Diseasesmentioning
confidence: 99%
“…The normal fallopian tubes are not visualized on CT unless they are dilated with fluid, pus, or blood. 10 The identification of a well-visualized or dilated fallopian tube should prompt the radiologist to look for the underlying cause pathology. The normal fallopian tubes, however, may sometimes be seen in the presence of ascites.…”
Section: Fallopian Tubesmentioning
confidence: 99%
“…14 There exists considerable overlap between the imaging appearances of hemorrhagic and luteal cysts, and the wall of corpus luteal cysts appears thicker than that of follicular cyst on the postcontrast study. 10…”
Section: Hemorrhagic Cystsmentioning
confidence: 99%